Quantum particle swarm optimization for economic dispatch problem using cubic function considering power loss constraint - Mahdi, F.P. (GEOMATE International Society, 2017)
In this paper, quantum computing (QC) inspired particle swarm optimization (QPSO) technique is utilized to solve economic dispatch (ED) problem, which has strong, robust and reliable search capability with powerful convergence properties. Here, authors use cubic criterion function to represent ED instead of the traditional quadratic function, to make the system robust against nonlinearities of actual power generators. Power balance, power loss and generator limit constraints are considered in this research work. To show the efficiency and robustness of the proposed method, authors have compared the obtained results with other algorithms like PSO and GA for ED problem on 3-unit and 5-unit power generating systems. The obtained results demonstrate QPSO's superiority over other methods in terms of providing quality solutions with significant amount of robustness and computationally efficiency. © Int. J. of GEOMATE.